Comunicación organizacional y su relación con el desempeño de los colaboradores de Movistar Multicentro - Los Olivos - 2017 - Tello Urcia, Brenda Lissette (2018)
This research work has been developed in the company Movistar Multicentro - Los Olivos, which is a local belonging to Telefónica del Perú, one of the leading companies in the field of telecommunications, own store that receives an average of 700 to 800 clients, the research was carried out by applying the collection instruments to the company's collaborators, analyzing the incidence of organizational communication and its implication in the performance of their tasks, with the objective of determining how organizational communication relates to performance of the collaborators of Movistar Multicentro - Los Olivos; the research was descriptive, not experimental, cross-sectional and correlational, the Inductive-Deductive Method, Hypothetical-Deductive Method was used, the survey was also used as a research technique, the Cronbach's Alpha method was used to verify the reliability of the data obtained, obtaining an alpha of 0.843 for the organizational communication variable, and 0.867 for the employee dependent performance variable; and the Pearson coefficient was used to establish the relationship of the organizational communication with the performance of the collaborators of Movistar Multicentro - Los Olivos whose result was a correlation index of r = 0.84; concluding that there is a positive relationship between the variables of interest, and that as organizational communication improves, it implies improvement of the employees' performance; for the development of the research work, the population was made up of the collaborators of Empresa Movistar Multicentro - Los Olivos, a representative sample of 80 collaborators was obtained by means of the statistical method, then the data collection instruments were applied, reaching the main conclusion that the organizational communication is positively related to the performance of the employees of Movistar Multicentro - Los Olivos - 2017.